2020
DOI: 10.7554/elife.50294
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structures of S-OPA1 reveal its interactions with membrane and changes upon nucleotide binding

Abstract: Mammalian mitochondrial inner membrane fusion is mediated by optic atrophy 1 (OPA1). Under physiological conditions, OPA1 undergoes proteolytic processing to form a membrane-anchored long isoform (L-OPA1) and a soluble short isoform (S-OPA1). A combination of L-OPA1 and S-OPA1 is essential for efficient membrane fusion; however, the relevant mechanism is not well understood. In this study, we investigate the cryo-electron microscopic structures of S-OPA1–coated liposomes in nucleotide-free and GTPγS-bound stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 51 publications
3
47
0
Order By: Relevance
“…Parallel investigations of the cryo-EM structure of liposomes coated with human S-OPA1, as well as X-ray crystallography of the yeast S-Mgm1 support the findings made about fungal Mgm1 protein regarding the importance of its oligomerization, GTPase function activation, domain structure, and its membrane curvature induction activity (Zhang et al 2020). Sequence analysis of the human S-OPA1 as well as yeast S-Mgm1 suggest that their C-terminal domains (corresponding to the paddle domain of Chaetomium Mgm1) exert membrane binding and deformation via an AH.…”
Section: Mgm1/opa1-cristae Membranessupporting
confidence: 60%
See 1 more Smart Citation
“…Parallel investigations of the cryo-EM structure of liposomes coated with human S-OPA1, as well as X-ray crystallography of the yeast S-Mgm1 support the findings made about fungal Mgm1 protein regarding the importance of its oligomerization, GTPase function activation, domain structure, and its membrane curvature induction activity (Zhang et al 2020). Sequence analysis of the human S-OPA1 as well as yeast S-Mgm1 suggest that their C-terminal domains (corresponding to the paddle domain of Chaetomium Mgm1) exert membrane binding and deformation via an AH.…”
Section: Mgm1/opa1-cristae Membranessupporting
confidence: 60%
“…Liposome co-sedimentation assays with recombinantly purified short isoform of OPA1 revealed a strong binding preference to the negatively charged liposomes containing, for example, phosphatidylserine (PS) or cardiolipin (CL) (Ban et al 2010). Membrane binding promoted the rather low basal GTPase activity of OPA1 up to 100 folds, as well as assembly of OPA1 into higher order oligomers, as detected by homo-bifunctional cross-linking experiments (Ban et al 2010;Zhang et al 2020). Fluorescence microscopy, negative stain transmission EM, as well as electron cryo-microscopy showed that these higher order oligomers assemble into a regular pattern and induce protrusion of lipid tubules from the cardiolipin-containing liposomes (Frezza et al 2006;Ban et al 2010;Zhang et al 2020).…”
Section: Mgm1/opa1-cristae Membranesmentioning
confidence: 96%
“…This may indicate that Opa1 processing is not necessary for fusion, and that overexpression of short OPA1 forms trigger mitochondrial fragmentation in Yme1l −/− cells (61). However, recent studies show that S-OPA1 play a role in MIM fusion, and cryo-electron microscopy (cryo-EM) studies reveal that S-OPA1 has a dynamin-like structure and employs dynamin-like power stroke membrane remodeling for MIM fusion (62). Moreover, moderate levels of S-OPA1 together with L-OPA1 are required for efficient and fast membrane pore opening during the fusion process, but excess levels of S-OPA1 inhibit fusion activity (63).…”
Section: The Mammalian Mitochondrial Fusion Machinerymentioning
confidence: 99%
“…The unique ability of S-Mgm1 to form a helical lattice on the outside and inside of lipid tubes, in combination with flexibility to form either left-or right-handed helices, could explain the multifaceted activity of S-Mgm1 in coordinating fusion and fission of IM in addition to controlling cristae width. Cryo-ET revealed that addition of S-OPA1 to liposomes tubulated them via the formation of helical lattices independently of S-OPA1 GTPase activity [50]. Moreover, studies in baker's yeast have led to the Oxidative phosphorylation (OXPHOS): the process in which NADH/FADH 2 are oxidized to generate the proton motive force used for formation of ATP employing respiratory chain complexes I to IV as well as complex V, the F 1 F o ATP synthase.…”
Section: Opa1 As the Regulator Of Cristae Remodeling: New Roles For Amentioning
confidence: 99%